A guideline for the use of variable rate intravenous insulin infusion in medical inpatients. Issue 6 (June 2015) - George, S.; Dale, J.; Stanisstreet, D.; the Joint British Diabetes Societies (JBDS) for Inpatient Care; the JBDS Medical VRIII Writing Group
Abstract The present paper summarizes the key recommendations in a recent publication produced by the Joint British Diabetes Societies for Inpatient Care on the use of variable rate i.v. insulin infusion in 'medical' inpatients. The full guideline is available at http://www.diabetologists-abcd.org.uk/JBDS/JBDS_IP_VRIII.pdf and is designed to be a practical guide that can used by any healthcare professional who manages medical inpatients with hyperglycaemia. Its main aim is to allow variable rate i.v. insulin infusion to be used safely, effectively and efficiently for this specific group of inpatients.